Botany, sexuality and women's writing, 1760-1830 : From modest shoot to forward plant - George, Sam, Dr (Book collections on Project MUSE., 2018)
In this fascinating study, Samantha George explores the cultivation of the female mind and the feminised discourse of botanical literature in eighteenth-century Britain. In particular, she discusses British women's engagement with the Swedish botanist, Carl Linnaeus, and his unsettling discovery of plant sexuality. Previously ignored primary texts of an extraordinary nature are rescued from obscurity and assigned a proper place in the histories of science, eighteenth-century literature, and women's writing. The result is groundbreaking: the author explores nationality and sexuality debates in relation to botany and charts the appearance of a new literary stereotype, the sexually precocious female botanist. She uncovers an anonymous poem on Linnaean botany, handwritten in the eighteenth century, and subsequently traces the development of a new genre of women's writing - the botanical poem with scientific notes. The book is indispensable reading for all scholars of the eighteenth century, especially those interested in Romantic women's writing, or the relationship between literature and science.